Neuroprotective and anti-inflammatory properties of proteins secreted by glial progenitor cells derived from human iPSCs - Salikhova, Diana I.; Shedenkova, Margarita O.; Sudina, Anastasya K.; Belousova, Ekaterina V.; Krasilnikova, Irina A.; Nekrasova, Anastasya A.; Nefedova, Zlata A.; Frolov, Daniil A.; Fatkhudinov, Timur Kh.; Makarov, Andrey V.; Surin, Alexander M.; Savostyanov, Kirill V.; et al. (Frontiers in Cellular Neuroscience, 2024)
Curently, stem cells technology is an effective tool in regenerative medicine. Cell therapy is based on the use of stem/progenitor cells to repair or replace damaged tissues or organs. This approach can be used to treat various diseases, such as cardiovascular, neurological diseases, and injuries of various origins. The mechanisms of cell therapy therapeutic action are based on the integration of the graft into the damaged tissue (replacement effect) and the ability of cells to secrete biologically active molecules such as cytokines, growth factors and other signaling molecules that promote regeneration (paracrine effect). However, cell transplantation has a number of limitations due to cell transportation complexity and immune rejection. A potentially more effective therapy is using only paracrine factors released by stem cells. Secreted factors can positively affect the damaged tissue: promote forming new blood vessels, stimulate cell proliferation, and reduce inflammation and apoptosis. In this work, we have studied the anti-inflammatory and neuroprotective effects of proteins with a molecular weight below 100 kDa secreted by glial progenitor cells obtained from human induced pluripotent stem cells. Proteins secreted by glial progenitor cells exerted anti-inflammatory effects in a primary glial culture model of LPS-induced inflammation by reducing nitric oxide (NO) production through inhibition of inducible NO synthase (iNOS). At the same time, added secreted proteins neutralized the effect of glutamate, increasing the number of viable neurons to control values. This effect is a result of decreased level of intracellular calcium, which, at elevated concentrations, triggers apoptotic death of neurons. In addition, secreted proteins reduce mitochondrial depolarization caused by glutamate excitotoxicity and help maintain higher NADH levels. This therapy can be successfully introduced into clinical practice after additional preclinical studies, increasing the effectiveness of rehabilitation of patients with neurological diseases.